Hydroxyapatite Powders from Chicken Bone Waste: Effect of Low and High-Temperature Calcination - Abd Rahman, Mohamad Razif; Muhammad Izra Salzamizar Mohd Salehin; Che Murad, Mardziah; Mohamed Kamal Abbas (International Journal of Integrated Engineering, 2024)
Hydroxyapatite (HA) is a calcium phosphate-based substance that closely mimics the structure and chemical composition of natural bone. Its properties can vary depending on the preparation method and the origin of the precursors. This study aims to thoroughly investigate the properties of HA powders derived from chicken bone waste, obtained at different calcination temperatures. To achieve this, the chicken bones underwent a meticulous cleaning process followed by air drying. Subsequently, the dried bones were finely crushed into smaller pieces and subjected to calcination at 600°C (HA-600) and 1000°C (HA-1000) for comparison. The resulting HA powders were then characterised using a range of analytical techniques, including X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and Brunauer-Emmett-Teller (BET) analysis and Field emission scanning electron microscopy (FESEM). The XRD analysis uncovered that HA-600 exhibited a low crystalline HA component, whereas HA-1000 displayed a highly crystalline structure that consists of two distinct phases: HA and beta-tricalcium phosphate (β-TCP). Nonetheless, functional groups such as hydroxyl, phosphate, and carbonate were detected in the FTIR spectra, confirming the formation of HA as the dominant phase in both samples. Additionally, BET analysis disclosed that the average total surface area of the samples was measured as 26.933 cm3/g and 6.896 cm3/g for HA-600 and HA-1000, respectively, implying that the powder particles are relatively larger in size for sample calcinated at higher temperature.Top of Form These findings indicate that subjecting chicken bone-derived HA to high-temperature calcination plays a pivotal role in shaping its properties. This process can be fine-tuned for optimal results, yielding bio-ceramic materials tailored to meet specific requirements in various biomedical applications.